A high conductivity enhanced composite carbon paper and its preparation method and application

By forming a resin impregnation mixture of phenolic resin and chitosan on the surface of the carbon paper and performing multiple steps to prepare high-conductivity enhanced composite carbon paper, the problem of insufficient conductivity and strength of existing carbon fiber paper is solved, and the Performance improvements and cost reductions.

CN118486841BActive Publication Date: 2025-02-25TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410680009.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-02-25
Estimated Expiration
2044-05-29

Smart Images

  • Figure CN118486841B_ABST
    Figure CN118486841B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, in particular to a highly conductive enhanced composite carbon paper and a preparation method and application thereof, wherein the preparation method is as follows: providing a carbon paper; forming a resin impregnation mixture on the surface of the carbon paper, wherein the resin impregnation mixture contains a phenolic resin and chitosan; sequentially performing a degassing treatment, a drying treatment, a hot pressing treatment, and a curing treatment on the carbon paper with the resin impregnation mixture formed on the surface obtained in the previous step to obtain a cured carbon paper; performing a heat treatment on the cured carbon paper to obtain a highly conductive enhanced composite carbon paper; the composite carbon paper can be used as a gas diffusion layer of a fuel cell. Compared with the prior art, the highly conductive enhanced composite carbon paper proposed by the present invention has both lower cost and better conductivity and strength, and the preparation method is simple and easy to implement, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, in particular to a highly conductive enhanced composite carbon paper and a preparation method and application thereof. Background Art

[0002] Carbon fiber paper is a carbon / carbon composite material with chopped carbon fiber as the skeleton and thermosetting resin as the binder. It is mainly used as a gas diffusion layer in fuel cells, playing the role of mass transfer, electrical conduction, heat transfer, and supporting the catalyst layer. It is one of the indispensable materials for fuel cells. Its common manufacturing method is: the carbon fiber base paper obtained by wet papermaking is impregnated in a phenolic resin solution, and then obtained after drying, curing and carbonization. The phenolic resin solution has a high bonding strength, and has good compatibility with various inorganic and organic fillers, and a fast wetting speed. However, the residual carbon rate is not high, which affects its conductivity and strength, and then limits its application.

[0003] In the prior art, Japan's Toray carbon paper is widely used, which has high conductivity, high strength, corrosion resistance and excellent air permeability, but is expensive, about 10,000 per square meter. The carbon fiber paper commonly available in the domestic market is cheap, but has defects such as low strength, poor conductivity, easy dispersion at high temperature, and excessive porosity. If the cheap carbon fiber paper on the domestic market is reprocessed, its mechanical strength and conductivity can be improved at a lower cost, and low-priced, highly conductive, and high-strength domestic carbon fiber paper can be obtained, it will help break the commercial monopoly of imported carbon paper, especially Japan's Toray carbon paper, and promote the development of domestic fuel cell technology.

[0004] To this end, this application is filed. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a highly conductive enhanced composite carbon paper and a preparation method thereof.

[0006] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0007] On the one hand, the present invention provides a method for preparing a highly conductive enhanced composite carbon paper, comprising the following steps:

[0008] S1. Provide a carbon paper;

[0009] S2, forming a resin impregnation mixture on the surface of the carbon paper, wherein the resin impregnation mixture contains phenolic resin and chitosan;

[0010] S3, sequentially performing a degassing treatment, a drying treatment, a hot pressing treatment, and a curing treatment on the carbon paper with the resin impregnated mixture formed on the surface obtained in the previous step to obtain a cured carbon paper;

[0011] S4, heat-treating the cured carbon paper to obtain a highly conductive enhanced composite carbon paper.

[0012] In the application of carbon fiber paper, its conductivity and strength are the two most basic performance parameters. The performance of carbon paper made by wet process mainly depends on the strength of the carbon fiber itself and the binder used for impregnation. The strength of the carbon fiber base paper obtained after wet papermaking has been finalized. The present invention unexpectedly found that the surface of the existing carbon fiber paper is formed into a resin impregnation mixture containing phenolic resin and chitosan, and then subjected to degassing treatment, drying treatment, hot pressing treatment, curing treatment and heat treatment, which can significantly improve the conductivity and strength, and significantly improve the air permeability of the carbon paper.

[0013] In the above embodiment, if the density of the raw carbon paper used is too low, the porosity will be too high, which will make the strength of the carbon paper poor and easily cause gas leakage, excessive electrolyte liquid penetration and other problems, affecting the performance and life of the fuel cell. If the density of the carbon paper is too high, the porosity will be too low, affecting the air permeability. Therefore, the density of the carbon paper needs to be within a certain range. At present, the density of most existing carbon fiber papers on the market is between 5-50g / m 2 Through experiments, it is confirmed that carbon paper within the above density range is suitable for this application, among which 20-50g / m 2 , more preferably 30g / m 2 Theoretically, this preparation method is suitable for materials with a density lower than 5g / m 2 Or higher than 50g / m 2 Carbon paper is also applicable, but it is limited by the electrode weight requirements, and the loading amount of the resin impregnated mixture will have corresponding requirements.

[0014] In the above embodiment, the carbon paper is a single-layer or multi-layer stacking structure, preferably a two-layer stacking structure. The more layers of carbon paper there are, the better the conductivity of the obtained composite carbon paper, but the mechanical properties become worse; the fewer layers of carbon paper there are, the better the mechanical properties of the obtained composite carbon paper, but the conductive properties become worse; when a two-layer carbon paper stacking structure is adopted, the composite carbon paper obtained by the preparation method has both good conductive properties and mechanical properties.

[0015] Specifically, in S2, the resin impregnation mixture is a neutral mixture containing phenolic resin and chitosan, and the mass ratio of the phenolic resin to the chitosan is (5-40):1, preferably (10-30):1, and further preferably 20:1; the concentration of the resin impregnation mixture is 0.05-0.25 g / ml, preferably 0.1-0.2 g / ml, and further preferably 0.16 g / ml.

[0016] In the present embodiment, the phenolic resin and chitosan in the resin impregnation mixture are required to be mixed with a specific ratio. If phenolic resin is too much, its strong bonding force will bond chitosan and carbon fiber too tightly together and form a block stack, and the strong stress caused by the block stacking will make carbon paper easy to break, and the carbon paper strength cannot meet the use needs; if phenolic resin is too little, it cannot form an effective bonding effect to chitosan, causing the carbon fiber finally formed to be very loose, when phenolic resin and chitosan are mixed according to mass ratio for (5-40): 1, the bonding force of phenolic resin to chitosan is moderate, and the carbon fiber formed is dense, breathable and has a higher tensile strength at break.

[0017] In this embodiment, the concentration of the resin impregnation mixture is required to be within a certain range. If the resin impregnation mixture is too concentrated or too diluted, it is not conducive to maintaining good wettability on the carbon paper.

[0018] In this embodiment, the phenolic resin is preferably a water-soluble phenolic resin, which is a thermoplastic resin. The amount of the catalyst NaOH used in the synthesis process is small, and its pH value can be easily adjusted to neutral after preparation.

[0019] In this embodiment, chitosan can be water-soluble chitosan or water-insoluble chitosan. Considering the uniformity of the formed resin impregnation mixture, water-soluble chitosan is preferred. If water-insoluble chitosan is selected, it is preferred to prepare an aqueous solution of phenolic resin and an acidic aqueous solution of chitosan separately (acid needs to be added dropwise to promote the dissolution of chitosan when preparing the aqueous solution of chitosan), then mix the aqueous solution of phenolic resin and the acidic aqueous solution of chitosan evenly, and adjust the pH value to neutral; it should be noted that: since water-insoluble chitosan will be partially precipitated after the system pH is neutral, the concentration of the resin impregnation mixture mentioned above specifically refers to the ratio of the total mass g of phenolic resin and chitosan to the volume ml of solvent deionized water, and does not refer to the part of solute dissolved in deionized water alone. Of course, phenolic resin and chitosan can also be directly added to deionized water and acid can be added to promote the dissolution of chitosan to obtain a uniform solution, and then the pH value can be adjusted to neutral to ensure that the final carbon paper is neutral, and then maintain stable chemical and physical properties in the application, such as corrosion resistance, stability, conductivity, and avoid chemical reactions with other substances. As for what chemical substance to use to adjust the pH value, dilute hydrochloric acid, dilute sulfuric acid or sodium hydroxide aqueous solution can be selected according to actual needs.

[0020] Specifically, in S2, the resin impregnation mixture is formed on the surface of the carbon paper by brushing, and before brushing, the surface of the carbon paper is first brushed with ethanol to wet it, and the surface wetting helps the resin impregnation mixture to enter the interior of the carbon paper;

[0021] When the carbon paper is a single layer, the upper and lower surfaces of the carbon paper are first brushed with ethanol to moisten the upper and lower surfaces, and then the wetted upper and lower surfaces are brushed with the resin impregnation mixture; when the carbon paper is a multi-layer stacking structure, the upper and lower surfaces of the multi-layer stacking structure are first brushed with ethanol, and then the upper and lower surfaces of the multi-layer stacking structure are brushed with the resin impregnation mixture.

[0022] Specifically, the resin impregnation mixture should not be applied too much or too little. If it is applied too much, the residual carbon rate will be too large. Although it helps to improve the conductivity, the residual carbon adhesion will be poor and the thickness will be too thick, which will easily accumulate and produce strong stress, causing it to break easily; if it is applied too little, the residual carbon rate and adhesion cannot be significantly improved, and the conductivity and strength of the carbon paper will not be significantly improved. Several experiments have confirmed that in S2, the mass ratio of the resin impregnation mixture used for brushing to the carbon paper is (30-70):1, preferably (55-65):1, and further preferably 60:1. Within this range, the phenolic resin and chitosan in the resin impregnation mixture work synergistically to significantly improve the residual carbon rate, which helps to obtain good conductivity and strength.

[0023] Specifically, in S3: the specific operation of the degassing treatment is: placing the carbon paper with the resin impregnated mixture formed on the surface in a vacuum drying oven for vacuuming; the specific operation of the drying treatment is: taking out the carbon paper after the degassing treatment, placing the carbon paper on a container such as a tray and letting it stand to dry, turning the carbon paper during the drying process to keep the resin impregnated mixture on the upper and lower surfaces of the carbon paper uniform, and avoiding it from sticking to the tray or other containers; the specific operation of the hot pressing treatment is: using a hot press to hot press the carbon paper after the drying treatment, the hot pressing conditions are 50-300℃, 0.1-1MPa hot pressing for 10-1800s, preferably 50-150℃, 0.2-0.6MPa hot pressing for 30-600s, and more preferably 100℃, 0.3MPa hot pressing for 30s; the specific operation of the curing treatment is: curing at 100-160℃ for 2-24h, preferably 120-150℃ for 6-12h, and more preferably 150℃ for 12h.

[0024] Specifically, in S4, the heat treatment includes pre-carbonization and graphitization; the specific operation of pre-carbonization is: pre-carbonization is carried out in a tubular furnace, first ventilating for 2-10 hours under an inert atmosphere, then heating to 800-1100°C at a heating rate of 1-10°C / min, and then keeping warm for 2-3 hours under an inert atmosphere to obtain a carbon fiber paper precursor; preferably, first ventilating for 4-8 hours under an inert atmosphere, then heating to 900-1000°C at a heating rate of 3-7°C / min, then keeping warm for 2-3 hours under an inert atmosphere, and further preferably, first ventilating for 6 hours under an inert atmosphere, and then heating to 900°C, and then keep warm for 2h under inert atmosphere; the specific operation of graphitization is: graphitization is carried out in a hot pressing furnace, the temperature is increased to 1700-2200°C at a heating rate of 2-20°C / min, and then kept warm for 0.5-5h under working pressure 2-10MPa and vacuum conditions; preferably, the temperature is increased to 1900-2100°C at a heating rate of 8-15°C / min, and then kept warm for 1-2h under working pressure 4-8MPa and vacuum conditions; further preferably, the temperature is increased to 1900°C at a heating rate of 10°C / min, and then kept warm for 1h under working pressure 5MPa and vacuum conditions.

[0025] In the previous embodiment, in order to further remove impurities in the carbon paper and the raw materials and make the graphitization treatment more stable, the heat treatment preferably also includes secondary carbonization. The specific operation of the secondary carbonization is: secondary carbonization is carried out in a tubular furnace, first ventilating for 2-10 hours under an inert atmosphere, then heating to 1300-1600°C at a heating rate of 1-10°C / min, and then keeping warm for 1-5 hours under an inert atmosphere; preferably, first ventilating for 2-5 hours under an inert atmosphere, then heating to 1450-1550°C at a heating rate of 3-7°C / min, and then keeping warm for 2-4 hours under an inert atmosphere, and further preferably, first ventilating for 3 hours under an inert atmosphere, then heating to 1500°C at a heating rate of 5°C / min, and then keeping warm for 3 hours under an inert atmosphere.

[0026] It should be noted that secondary carbonization is not a necessary heat treatment step and can be flexibly selected according to needs in specific practice. If the purity of the original carbon paper and other raw materials is high, there is no need to perform secondary carbonization. If the purity of the original carbon paper and other raw materials is slightly lower, it is safer to perform secondary carbonization.

[0027] On the other hand, the present invention provides a highly conductive enhanced composite carbon paper prepared by the above preparation method.

[0028] In addition, the present invention also provides a fuel cell, which uses the above-mentioned highly conductive enhanced composite carbon paper as a gas diffusion layer.

[0029] In addition, the highly conductive enhanced composite carbon paper has the characteristics of light weight, high conductivity, high strength, high temperature resistance, etc. It has broad application prospects and can also be used in aerospace, automotive industry, new energy, electronics and other fields, such as electrode materials for lithium batteries, electromagnetic shielding materials in the electronics field, etc., which are not further explored in the present invention.

[0030] Compared with the prior art, the highly conductive enhanced composite carbon paper proposed in the present invention has lower cost and better conductivity and strength, and the preparation method is simple and easy to implement, and the preparation process can be scaled up in proportion, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0032] Figure 1 SEM images of the carbon paper surface: a is phenolic carbon paper, b is chitosan carbon paper, and c is phenolic chitosan composite carbon paper.

[0033] Figure 2 This is the XRD comparison diagram of phenolic carbon paper and phenolic chitosan composite carbon paper after pre-carbonization.

[0034] Figure 3 This is a photo of chitosan carbon paper.

[0035] Figure 4 These are photographs of the bending fracture test of phenolic carbon paper and phenolic chitosan composite carbon paper: a is a photograph of the phenolic chitosan composite carbon paper at its bending limit, b is a photograph of the phenolic chitosan composite carbon paper at the moment of fracture, c is a photograph of the phenolic carbon paper at its bending limit, and d is a photograph of the phenolic carbon paper at the moment of fracture. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0037] In the following examples and comparative examples, the carbon paper used as raw material is specifically carbon fiber surface felt, the source information is: Changzhou Hualike, model C05-C50, density 5-50g / m 2 (Model corresponds to density, such as density 5g / m 2Corresponding model C05, density 10g / m 2 Corresponding model C10, and so on), strength 0.04-0.1MPa, resistance value 4-22Ω / 100mm, tensile strength 8.6-21N / 50mm, price 10-28 yuan / m 2 Other raw materials were commercially available and are not particularly limited. The devices used in the following examples and comparative examples, unless otherwise specified, are conventional devices in the art.

[0038] Example 1

[0039] S1, purchased from Changzhou Huali Ke, model C30, density 30g / m 2 The carbon fiber felt is used as the raw material, and it is cut into square pieces of 23cm×23cm. Two square pieces of the same size are stacked together so as to completely overlap and placed on a PP pallet for later use;

[0040] S2. Add water-soluble phenolic resin powder and water-soluble chitosan powder to deionized water in a mass ratio of 20:1 to prepare a resin impregnation mixture with a concentration of 0.16 g / ml, and adjust the pH value of the resin impregnation mixture to 7 by dropwise adding 10% by mass dilute hydrochloric acid; first, evenly brush the upper and lower surfaces of two stacked carbon fiber felts with 10 ml of ethanol to wet the upper and lower surfaces, and then evenly brush the resin impregnation mixture on the upper and lower surfaces, and the ratio of the mass of the resin impregnation mixture to the total mass of the two carbon fiber felts is 60:1;

[0041] S3, placing the product after the previous step in a vacuum drying oven, evacuating to remove bubbles in the carbon fiber felt, then taking it out and placing it on a PP tray to stand and dry, frequently turning the product during the standing process to prevent it from sticking to the PP tray, and performing hot pressing treatment using a hot press after it is dried. The conditions for hot pressing treatment are: hot pressing at 100°C and 0.3MPa for 30s, and then curing at 150°C for 12h to obtain cured carbon paper;

[0042] S4. The solid carbon paper is subjected to pre-carbonization, secondary carbonization and graphitization in sequence. The specific operation of pre-carbonization is as follows: first ventilate for 6 hours under an inert atmosphere, then heat to 900°C at a heating rate of 5°C / min, and then keep warm for 2 hours under an inert atmosphere; the specific operation of secondary carbonization is as follows: first ventilate for 3 hours under an inert atmosphere, then heat to 1500°C at a heating rate of 5°C / min, and then keep warm for 3 hours under an inert atmosphere; the specific operation of graphitization is as follows: heat to 1900°C at a heating rate of 10°C / min, and then keep warm for 1 hour under a working pressure of 5MPa and vacuum conditions; finally, a highly conductive enhanced composite carbon paper is obtained.

[0043] Example 2

[0044] Compared with Example 1, S1 uses a single layer of carbon fiber surface felt, and the rest is consistent with Example 1.

[0045] Example 3

[0046] Compared with Example 1, S1 uses three layers of carbon fiber surface felts with exactly the same size and specifications, and the three layers of carbon fiber surface felts are completely overlapped and stacked together, and the rest are consistent with Example 1.

[0047] Example 4

[0048] Compared with Example 1, the model of the carbon paper in S1 is adjusted to C05, and the rest are consistent with Example 1.

[0049] Example 5

[0050] Compared with Example 1, the model of the carbon paper in S1 is adjusted to C50, and the rest are consistent with Example 1.

[0051] Example 6

[0052] Compared with Example 1, the water-soluble chitosan is adjusted to water-insoluble chitosan, and the rest is the same as Example 1.

[0053] Example 7-Example 10

[0054] Compared with Example 1, the mass ratio of phenolic resin to chitosan in the resin impregnation mixture in Examples 7 to 10 was adjusted from 20:1 to 5:1, 10:1, 30:1, and 40:1, respectively, and the rest was consistent with Example 1.

[0055] Example 11-Example 14

[0056] Compared with Example 1, the concentration of the resin impregnation mixture in Examples 11 to 14 is adjusted from 0.16 g / ml to 0.05 g / ml, 0.1 g / ml, 0.2 g / ml, and 0.25 g / ml, respectively, and the rest remains the same as in Example 1.

[0057] Example 15-Example 18

[0058] Compared with Example 1, the mass ratio of the resin impregnated mixture to carbon paper during brushing in Examples 15 to 18 was adjusted from 60:1 to 30:1, 55:1, 65:1, and 70:1, respectively, and the rest remained consistent with Example 1.

[0059] Comparative Example 1

[0060] Compared with Example 1, the resin impregnation mixture only contains water-based phenolic resin, and the concentration of the water-based phenolic resin is the same as that of the water-based phenolic resin in Example 1. The rest is the same as Example 1.

[0061] Comparative Example 2

[0062] Compared with Example 1, the resin impregnation mixture only contains chitosan, and the concentration of chitosan is the same as that of chitosan in Example 1. The rest is the same as that in Example 1.

[0063] Comparative Example 3

[0064] Compared with Example 1, the mass ratio of phenolic resin to chitosan in the resin impregnation mixture is 1:1, and the rest is consistent with Example 1.

[0065] Comparative Example 4

[0066] Compared with Example 1, the mass ratio of phenolic resin to chitosan in the resin impregnation mixture is 50:1, and the rest is consistent with Example 1.

[0067] Comparative Example 5

[0068] Compared with Example 1, the concentration of the resin impregnation mixture is 0.02 g / ml, and the rest is consistent with Example 1.

[0069] Comparative Example 6

[0070] Compared with Example 1, the concentration of the resin impregnation mixture is 0.3 g / ml, and the rest is consistent with Example 1.

[0071] Comparative Example 7

[0072] Compared with Example 1, the mass ratio of the resin impregnated mixture used for brush coating to the carbon paper is 20:1, and the rest is consistent with Example 1.

[0073] Comparative Example 8

[0074] Compared with Example 1, the mass ratio of the resin impregnated mixture used for brush coating to the carbon paper is 80:1, and the rest is consistent with Example 1.

[0075] The important technical parameters of the above embodiments and comparative examples are shown in Table 1 below.

[0076] Table 1

[0077]

[0078]

[0079] In order to confirm that chitosan is successfully doped, the present invention performs elemental analysis on the products obtained in each embodiment and comparative example 1. Compared with comparative example 1, the oxygen content in the products obtained in each embodiment is significantly increased. Taking embodiment 1 as an example: the proportions of C, N, and O in the product of comparative example 1 (without chitosan) are 87.58at%, 1.02at%, and 11.4at%, respectively; the proportions of C, N, and O in the product of embodiment 6 (with chitosan) are 65.49at%, 1.27at%, and 33.24at%, respectively. Obviously, the oxygen content in the product of embodiment 6 has increased significantly, indicating that chitosan has been successfully doped.

[0080] like Figure 2 As shown: the phenolic carbon paper (the product of comparative example 1) and the phenolic chitosan composite carbon paper (the product of example 6) are compared, and both have a carbon peak at 24.3°, indicating that both carbon papers form carbon after carbonization. In addition, the phenolic chitosan carbon paper contains a characteristic peak of NaCl, and the phenolic carbon paper contains a characteristic peak of Na2S, which is due to the pH adjustment of the resin impregnation mixture during the preparation process.

[0081] Furthermore, the present invention explores the effect of phenolic chitosan compounding on the morphology of carbon paper. Figure 1 As shown: a, b, c are SEM images of the surface of phenolic carbon paper (the product of comparative example 1), chitosan carbon paper (the product of comparative example 2) and phenolic chitosan composite carbon paper (the product of example 6), respectively. From a, it can be seen that: when only phenolic resin is added to the resin impregnation mixture, phenolic forms large blocks on the surface of carbon fibers, and the strong bonding force of phenolic tightly bonds the carbon fibers together. Large blocks in some areas are stacked together without obvious gaps. In the subsequent tensile test, the block stacking area will produce strong stress and then break. From b, it can be seen that: when only chitosan is added to the resin impregnation mixture, since chitosan has no bonding effect, the fibers are loose after carbonization treatment, and chitosan is scattered on the fiber surface in the form of flakes and blocks. The product photo is shown in FIG. Figure 3 As shown; from c, it can be seen that when the resin impregnation mixture contains both phenolic resin and chitosan, the phenolic resin and chitosan are combined to retain more gaps between the block structures. The presence of the gaps helps the carbon paper maintain good air permeability. At the same time, some fibers are linear with a certain degree of curvature. The linear structure with a degree of curvature helps the carbon paper maintain a high tensile strength at break. In order to facilitate intuitive understanding of the difference in tensile strength at break between phenolic carbon paper and phenolic chitosan composite carbon paper, the present invention photographed Figure 4 The photos of the bending fracture test of the two carbon papers shown in the figure show that the phenolic chitosan composite carbon paper has better toughness than the phenolic carbon paper. Obviously, the addition of chitosan has a significant toughening effect.

[0082] The composite carbon papers obtained in Examples 1 to 18 and Comparative Examples 1 to 8 were subjected to relevant performance tests. The specific test methods are as follows: 1. Thickness measurement was performed using a digital micrometer thickness gauge 32CHQF1030; 2. A self-made standard of 1*1 cm was used. 2 The resistance measuring model with copper foil was placed on the carbon paper, 0.1Mpa pressure was applied to the model, and a multimeter was clamped at both ends of the model to obtain the corresponding resistance value; 3. The tensile test of carbon paper was carried out according to GB / T 20042.7 Proton Exchange Membrane Fuel Cell Part 7 Carbon Characteristics Test Method to obtain the tensile strength at break. The test results are shown in Table 2 below.

[0083] Table 2

[0084]

[0085]

[0086] From Table 1 and Table 2, we can see that:

[0087] From the comparison of the test results of Example 1, Comparative Example 1, and Comparative Example 2, it can be seen that when only chitosan is added to the resin impregnation mixture, the average resistance, average tensile strength at break, and average thickness of the obtained product are 12.36Ω, 5.49MPa, and 0.225mm, respectively; when only water-based phenolic resin is added to the resin impregnation mixture, the average resistance, average tensile strength at break, and average thickness of the obtained product are 0.61Ω, 10.8MPa, and 0.333mm, respectively; and when the resin impregnation mixture contains both water-based phenolic resin and water-based chitosan, the average resistance, average tensile strength at break, and average thickness of the obtained product are 0.49Ω, 24.21MPa, and 0.363mm, respectively. Obviously, adding water-based phenolic resin and water-based chitosan at the same time can not only further reduce the average resistance value and improve the conductivity of the product, but also significantly improve the strength of the carbon paper. Compared with only containing phenolic resin, the average tensile strength at break of the carbon paper after adding chitosan is doubled.

[0088] From the comparison of the test results of Example 1, Example 2, and Example 3, it can be seen that: under the premise that other conditions are completely consistent, when the raw material is double-layered, the average resistance, average tensile strength at break, and average thickness of the obtained product are 0.49Ω, 24.21MPa, and 0.363mm, respectively; when the raw material is single-layered, the average resistance, average tensile strength at break, and average thickness of the obtained product are 0.78Ω, 25.42MPa, and 0.152mm, respectively; when the raw material is only three layers, the average resistance, average tensile strength at break, and average thickness of the obtained product are 0.48Ω, 9.17MPa, and 0.528mm, respectively. Obviously, the more layers there are, the lower the average resistance of the product, the better the conductivity, but the smaller the average tensile strength at break. Although the conductivity is further improved when there are three layers, the degree of improvement is very limited, and the average tensile strength at break drops drastically, so it is preferably two layers, and the product obtained when there are two layers has both good conductivity and strength.

[0089] From the comparison of the test results of Example 1, Example 4, and Example 5, it can be seen that: under the premise that other conditions are completely the same, when the density of the raw material is 5g / m 2 When the density of the raw material is 30g / m 2 When the density of the raw material is 50g / m 2 When the average resistance and average tensile strength at break of the obtained product are 0.52Ω and 13.21MPa, respectively. Obviously, no matter how much the raw material density is, after being processed by the preparation method proposed by the present invention, the average resistance is significantly reduced, the conductivity is significantly improved, and the average tensile strength at break is significantly improved; wherein, the raw material density is selected to be 30g / m 2 The performance of the obtained product is best.

[0090] From the comparison between Example 1 and Example 6, it can be seen that, under the premise that other conditions are exactly the same, the use of water-soluble chitosan is better than the use of non-water-soluble chitosan. The reason for this should be that water-soluble chitosan has better solubility and dispersibility in the resin impregnation mixture, which ultimately makes a large number of curved linear fibers evenly distributed on the carbon paper, thereby fully improving the conductivity and tensile strength of the carbon paper.

[0091] From the comparison of the test results of Example 1, Example 7-Example 10, Comparative Example 3, and Comparative Example 4, it can be seen that: when the mass ratio of phenolic resin to chitosan is less than 5:1, such as 1:1 (Comparative Example 3), the strength of the obtained product is higher, but the conductivity is poor. When the mass ratio of phenolic resin to chitosan is greater than 40:1, such as 50:1 (Comparative Example 4), the conductivity of the obtained product is better, but the strength is poor. When phenolic resin and chitosan are mixed according to the mass ratio (5-40):1, the bonding force of phenolic resin to chitosan is moderate, the carbon fiber formed is dense, breathable and has a higher tensile strength at break, and the product has excellent conductivity and strength, wherein (10-30):1 is preferred, and 20:1 is more preferred.

[0092] From the comparison of the test results of Example 1, Example 11-Example 14, Comparative Example 5, and Comparative Example 6, it can be seen that if the concentration of the resin impregnation mixture is less than 0.05g / ml, such as 0.02g / ml (Comparative Example 5), the conductivity of the obtained product is slightly poor, and if the concentration of the resin impregnation mixture is greater than 0.25g / ml, such as 0.3g / ml (Comparative Example 6), the average tensile strength at break of the obtained product is unsatisfactory. The suitable concentration of the resin impregnation mixture is 0.05-0.25g / ml, preferably 0.1-0.2g / ml, and more preferably 0.16g / ml. We speculate that within the above concentration range, the resin impregnation mixture has good wettability on carbon paper, which is convenient for it to adhere to the raw carbon paper and achieve a good carbonization effect.

[0093] From the comparison of the test results of Example 1, Example 15-Example 18, Comparative Example 7, and Comparative Example 8, it can be seen that: if the mass ratio of the resin impregnated mixture to the carbon paper during brushing is less than 30:1, such as 20:1, the conductivity of the product is poor, and if it is greater than 70:1, such as 80:1, the average tensile strength at break of the product is poor. The mass ratio of the resin impregnated mixture to the carbon paper used for brushing is (30-70):1, preferably (55-65):1, and more preferably 60:1. Within this range, the phenolic resin in the resin impregnated mixture and chitosan work synergistically, which can significantly increase the residual carbon rate and help to obtain good conductivity and strength.

[0094] In summary: the high conductivity enhanced composite carbon paper proposed in the present invention has low cost and good conductivity and strength. The optimal embodiment can be comparable to Toray carbon paper. More importantly, it has a very high cost performance, and the preparation method is simple and easy to implement. The preparation process can be scaled up in proportion, which is conducive to industrial production.

[0095] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A method for preparing a highly conductive enhanced composite carbon paper, characterized in that: The steps are as follows: S1. Provide a carbon paper; S2, forming a resin impregnation mixture on the surface of the carbon paper, wherein the resin impregnation mixture is a neutral mixture containing a phenolic resin and chitosan, the mass ratio of the phenolic resin to the chitosan is (5-40):1, the concentration of the resin impregnation mixture is 0.05-0.25 g / ml, and the mass ratio of the resin impregnation mixture to the carbon paper is (30-70):1; S3, sequentially performing a degassing treatment, a drying treatment, a hot pressing treatment, and a curing treatment on the carbon paper with the resin impregnated mixture formed on the surface obtained in the previous step to obtain a cured carbon paper; S4, heat-treating the cured carbon paper to obtain a highly conductive enhanced composite carbon paper.

2. The method for preparing the highly conductive enhanced composite carbon paper according to claim 1, characterized in that: In S1, the density of the carbon paper is 5-50g / m 2 The carbon paper is a single-layer or multi-layer stacked structure.

3. The method for preparing the highly conductive enhanced composite carbon paper according to claim 1, characterized in that: The phenolic resin is a water-soluble phenolic resin, and the chitosan is a water-soluble chitosan.

4. The method for preparing the highly conductive enhanced composite carbon paper according to claim 1, characterized in that: In S2, the resin impregnation mixture is formed on the surface of the carbon paper by brushing, and before brushing, the surface of the carbon paper is first brushed with ethanol to wet it; When the carbon paper is a single layer, the upper and lower surfaces of the carbon paper are first brushed with ethanol to wet the upper and lower surfaces, and then the upper and lower surfaces of the carbon paper are brushed with the resin impregnated mixture; when the carbon paper is a multi-layer stacking structure, the upper and lower surfaces of the multi-layer stacking structure are first brushed with ethanol, and then the upper and lower surfaces of the multi-layer stacking structure are brushed with the resin impregnated mixture.

5. The method for preparing the highly conductive enhanced composite carbon paper according to claim 1, characterized in that: In S3: the specific operation of the degassing treatment is: placing the carbon paper with the resin impregnated mixture formed on the surface in a vacuum drying oven to evacuate; the specific operation of the drying treatment is: taking out the carbon paper after the degassing treatment, standing it to dry, and turning the carbon paper during the drying process to keep the resin impregnated mixture on the upper and lower surfaces of the carbon paper uniform, while preventing it from sticking to the container; the specific operation of the hot pressing treatment is: hot pressing the carbon paper after the drying treatment using a hot press, and the hot pressing conditions are 50-300℃, 0.1-1MPa, and hot pressing for 10-1800s; the specific operation of the curing treatment is: curing at 100-160℃ for 2-24h; In S4, the heat treatment includes pre-carbonization and graphitization; the specific operation of pre-carbonization is: pre-carbonization is carried out in a tubular furnace, first ventilated for 2-10 hours under an inert atmosphere, and then heated to 800-1100°C at a heating rate of 1-10°C / min, and then kept warm for 2-3 hours under an inert atmosphere to obtain a carbon fiber paper precursor; the specific operation of graphitization is: graphitization is carried out in a hot press furnace, the temperature is increased to 1700-2200°C at a heating rate of 2-20°C / min, and then kept warm for 0.5-5 hours under a working pressure of 2-10MPa and vacuum conditions.

6. The method for preparing the highly conductive enhanced composite carbon paper according to claim 5, characterized in that: In S4, the heat treatment also includes secondary carbonization. The specific operation of the secondary carbonization is: secondary carbonization is carried out in a tubular furnace, first ventilating for 2-10 hours under an inert atmosphere, then heating to 1300-1600°C at a heating rate of 1-10°C / min, and then keeping warm for 1-5 hours under an inert atmosphere.

7. A highly conductive enhanced composite carbon paper, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

8. A fuel cell, characterized in that: The highly conductive enhanced composite carbon paper as claimed in claim 7 is used as the gas diffusion layer.

Citation Information

Patent Citations

  • Composite carbon paper, preparation method and battery

    CN115874489A

  • Phenol resin-mixed papermaking sheet, its production and gasket composed of the same

    JP1998168782A